Lenvatinib for Anaplastic Thyroid Cancer - Tahara, Makoto; Kiyota, Naomi; Yamazaki, Tomoko; Chayahara, Naoko; Nakano, Kenji; Inagaki, Lina; Toda, Kazuhisa; Enokida, Tomohiro; Minami, Hironobu; Imamura, Yoshinori; Sasaki, Tatsuya; Suzuki, Takuya; et al. (Frontiers in Oncology, 2017)
Background Lenvatinib has been approved by regulatory agencies in Japan, the United States, and the European Union for treatment of radioiodine-refractory differentiated thyroid cancer (RR-DTC). Thyroid cancer, however, is a clinically diverse disease that includes anaplastic thyroid cancer (ATC), the subtype associated with the highest lethality. Effective therapy for ATC is an unmet need. Patients and methods This phase 2, single-arm, open-label study in patients with thyroid cancer, including ATC, RR-DTC, and medullary thyroid cancer was conducted from 3 September 2012 to 9 July 2015. Patients received lenvatinib 24 mg daily until disease progression or development of unacceptable toxicity. The primary endpoint was safety, and the secondary endpoint was efficacy, as assessed by progression-free survival (PFS), overall survival (OS), and objective response rate. Results At data cutoff, 17 patients with ATC were enrolled. All experienced ≥1 treatment-emergent adverse event (TEAE). The most frequent TEAEs were decreased appetite (82%), hypertension (82%), fatigue (59%), nausea (59%), and proteinuria (59%). Of note, only one patient required lenvatinib withdrawal because of a TEAE, and this TEAE was considered unrelated to lenvatinib. The median PFS was 7.4 months [95% confidence interval (CI): 1.7–12.9], the median OS was 10.6 months (95% CI: 3.8–19.8), and the objective response rate was 24%. Conclusion In this study, lenvatinib demonstrated manageable toxicities with dose adjustments and clinical activity in patients with ATC. This clinical activity of lenvatinib warrants further investigation in ATC. ClinicalTrials.gov NCT01728623.